2013
DOI: 10.1242/jeb.087601
|View full text |Cite
|
Sign up to set email alerts
|

Anemonefish oxygenate their anemone hosts at night

Abstract: There was an error published in J. Exp. Biol. 216,[970][971][972][973][974][975][976]. Fig. 3 included some additional text. The correct figure is displayed below. Fig.3. Effects of water flow rate on the dark maximum oxygen uptake (VO 2 ,max, mean ± 1 s.e.m.) of bulb-tentacle sea anemones (E. quadricolor) in flowthrough respirometry. Mean VO 2 ,max=114.21±13.89μmolO2h -1 . VO 2 ,max values at 0.5 and 1.0cms -1 were significantly different (*P<0.05).We apologise to the authors and readers for any confusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Regardless of its origin here, and whether or not it reflects a beneficial aspect of the symbiosis, the degree to which microbial communities differ in ARA functions is a striking metabolic signal that the microbial communities on host sea anemones are responding to clownfish presence. Minimally, this finding is consistent with the literature that clownfish presence has a significant impact on the metabolism and physiology of the host anemone [28-29; 47-48].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Regardless of its origin here, and whether or not it reflects a beneficial aspect of the symbiosis, the degree to which microbial communities differ in ARA functions is a striking metabolic signal that the microbial communities on host sea anemones are responding to clownfish presence. Minimally, this finding is consistent with the literature that clownfish presence has a significant impact on the metabolism and physiology of the host anemone [28-29; 47-48].…”
Section: Resultssupporting
confidence: 92%
“…Eicosanoid lipids participate in an oxidative stress response and are hypothesized to play a role in the oxidative stress response in symbiotic cnidarians [43-44]. It is well documented that clownfish symbionts increase gas transfer and oxygenate their host anemones while also passing organic wastes to their anemone hosts, which functionally act as fertilizers for endosymbiotic Symbiodiniaceae [28-29]. It is not inconceivable that the increase in oxygen free radicals produced by fish movements through the host, and by the oxygen produced as waste during photosynthesis, could stimulate a metabolic response by the host anemone that mimics an oxidative stress response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, we were successful in developing and field-testing a method for in situ induction of bleaching, which was the sole objective of this study. Anemonefish provide anemones with a range of benefits, including protection from predators and supply of oxygen and nutrients (Godwin & Fautin 1992;Cleveland et al 2011;Szczebak et al 2013). As a result, anemones that host anemonefish tend to live longer, grow faster and harbour higher densities of zooxanthellae, which have implications for the size and colour of anemones (Holbrook & Schmitt 2005;Porat & Chadwick-Furman 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Clownfish excretions can benefit the anemone. It has also been found that the clownfish at night fans water to the anemone and thus improves its oxygen supply [45]. A clownfish gets its anemone in its earliest days.…”
Section: Consanguinitymentioning
confidence: 99%